“Assessment of diabetes management strategies for blood glucose control in Sana’a City General Hospitals” - Salman Al-Shami, Ali; Alzumor, Mokhtar; Aladhal, Adnan; Al-Worafi, Yaser; Thawaba, Zaid A. (Frontiers in Endocrinology, 2025)
BackgroundDiabetes mellitus is a major global health concern associated with serious complications. Effective management of blood glucose levels is crucial in reducing these complications.ObjectivesThis study aimed to evaluate blood glucose management strategies among diabetic patients in general hospitals in Sana’a city, Yemen.MethodsA cross-sectional study was conducted involving 50 diabetic patients. Data on demographics, risk factors, treatment adherence, lifestyle habits, and biochemical markers were collected through questionnaires and laboratory tests. Statistical analysis was performed using SPSS.ResultsThe study found a higher prevalence of diabetes among males, individuals aged 41–60 years, married persons, and those who were illiterate. “Type 2 Diabetes Mellitus was more common than insulin-dependent diabetes mellitus (IDDM) (80% vs. 20%). Laboratory monitoring was the most commonly used management strategy, while adherence to treatment, exercise, and nutrition was lower. Patients adhering to treatment, exercise, and nutrition therapy showed significantly better clinical and biochemical profiles, including lower LDL, triglycerides, total cholesterol, HbA1c, fasting blood sugar, BMI, and blood pressure levels. The prevalence of diabetes complications was lower among patients who followed management protocols.ConclusionsRegular treatment adherence, exercise, nutrition therapy, and laboratory monitoring contribute to improved blood glucose control and reduce diabetes-related complications. Enhancing patient education and adherence to management strategies is essential for better clinical outcomes.